Transformasi Kantor Urusan Agama Biringkanaya Kota Makassar Melalui Program Pusaka Sakinah - Sugeng; Aris Munandar; Arief Halim; Ishak Shamad (Journal of Gurutta Education, 2022)
The Sakinah Heritage is an effort by the Directorate General of Islamic Guidance at the Ministry of Religion to transform the Office of Religious Affairs into a better direction through the synergy between Penghulu and Religious Counselors. The aim is to find out the extent of the Sakinah heritage program through the Office of Religious Affairs and the effectiveness of employee performance in improving the quality of marriage services in Makassar City. This research method uses qualitative methods with the reason that the questions are open so that researchers can be flexible and develop questions because researchers want to describe and analyze the implementation of the transformation of the Sakinah heritage program through the religious affairs office (KUA) in Makassar city. The results of research at the Biringkanaya religious affairs office show that the Biringkanaya sub-district religious affairs office has an area of 48.22 km2, a population of 234,632 people, and the number of marriage events/year is 1,063. Judging from the religion adopted, it is noted that the majority of the population of Biringkanaya Sub-district is Muslim. The number of places of worship is quite adequate. There are 266 mosques, 14 prayer rooms (langgar/surau), and 23 churches.